A FORMULATION OF HAND BODY LOTIO FORMULATION OF HAND BODY LOTION EXTRACT ethanol from lily leaves (Crinum asiaticum L.) AS A SKIN MOISTURIZER - barus, bunga rimta (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2024)
Lily leaves (Crinum asiaticum L.) have bioactivity as antioxidants and contain chemical compounds such as glycosides, flavonoids, saponins, tannins and triterpenoids. This study aims to formulate daffodil leaf extract into a hand body lotion dosage form and observe the effectiveness on volunteer skin for 4 weeks. This research was conducted experimentally. Samples were taken from daffodil leaves (Crinum asiaticum L.), then extracted by maceration with 96% ethanol and concentrated using a rotary evaporator. The ethanol extract of daffodil leaves was formulated with concentrations of 5%, 8% and 11%. The preparation evaluation test includes homogeneity, organoleptic, pH, emulsion type, irritation test, and effectiveness test of the preparation to moisturize the skin. The results showed that the ethanol extract of daffodil leaves could be used to make homogeneous grated emulsion preparations which were stable during 4 weeks of storage, pH 7.52-7.25, oil-in-water emulsion type and did not disappear. Any hand cream product that contains narcissus leaf ethanol can increase skin moisture. The composition of the most effective hand and body cream in the treatment of dry skin is a preparation with a concentration of 11% ethanol extract of lily leaves, which increases skin healing by 40.35% and is applied to the skin within 1 month.